Sureśvara's Vārtika on Jyotis Brāhmaṇa - Hino, Shoun; Jog, K. P. (Motilal Banarsidass Publishers, 2001)
Supercommentary on Śāṅkarācārya's commentary on Br̥hadāraṇyakopaniṣad; includes English translation.